2019
DOI: 10.1116/1.5115164
|View full text |Cite
|
Sign up to set email alerts
|

Increase of space width roughness in directed self-assembly patterning arising from shrinking stress in the remaining poly(methyl methacrylate)

Abstract: The mechanism for the increase in space width roughness (SWR) after selective poly(methyl methacrylate) (PMMA) etching to polystyrene (PS) is investigated for directed self-assembly patterning. Considering the cross-sectional image obtained from field-emission scanning electron microscopy, the authors propose a physical model where the shrinking stress in the remaining PMMA with thickness variation induces PS-line collapse and this collapse increases SWR. Linear finite-element calculations show that this propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In TFMHM, the TiN mask is exposed to plasma during the p-SiOCH etch. Plasma exposure is known to damage thin film surfaces and can induce compressive stress [8][9][10] . Thus, the stress of TiN films after plasma exposure was investigated in addition to intrinsic stress without any plasma exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In TFMHM, the TiN mask is exposed to plasma during the p-SiOCH etch. Plasma exposure is known to damage thin film surfaces and can induce compressive stress [8][9][10] . Thus, the stress of TiN films after plasma exposure was investigated in addition to intrinsic stress without any plasma exposure.…”
Section: Introductionmentioning
confidence: 99%
“…24) To address this issue, several studies have been conducted in recent years on systems that synchronize source pulsing and bias pulsing. [24][25][26][27][28][29][30][31] For example, it was reported that synchronized pulsing for both source power and bias power improved the profile difference between dense and isolated patterns because the pulsed plasma provided less dissociation due to lower electron temperature and plasma density. 32) Although the etching characteristics of the pulsing technique have been investigated in these studies, optimization of the parameters and their respective roles have not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%